Dra. Elenora Pencheva Directora Revista Europa del Este Unida - Pencheva, Elenora (Europa del Este Unida, 2021)
DEAR FRIENDS: The second issue of our magazine EUROPA DEL ESTE UNIDA was published. Thanks to all authors who supported us. There has gone another year full of dramatic and exciting events. Brazil experienced the removal of President Dilma Rusef. Venezuela continues the fight for preservation of the constitutional rights of its citizens. America elected a new president: Donald Trump. A few days ago the leader of the Cuban Revolution Fidel Castro has left us. In the 60s he is an example and hope for freedom and independence throughout Latin America. Cuba, despite the heroic struggle throughout the 19th century, remains a protectorate of the United States. It became a republic with the victory of the revolution in 1960. At last the wealth of Cuba belongs to the entire Cuban people. The island of freedom paid a high price for its independence: since the 60s of XX century it has been isolated from the United States, and since the '90 – from the former allies. Despite the enormous poverty the hope that it is possible to build a just society is not abandoned. The country does not accept the capitalism of inequality. Fidel was always for peace, peaceful cooperation and mutual understanding between the nations. With him goes a historical era - the revolutionary utopia and the boundless faith in the possible better society. There are different opinions about the way Fidel defended the socialist revolution. For some he will remain a dictator; for others - an idealist revolutionary who could not return Cuba again to capitalism against which he had fought. Despite poverty, Fidel did not accept the IMF with its "killer tips" that could bring the country into another debt spiral. Many people believe that after the death of Fidel, Cuba will become rich. Whether Cuban communists will follow the Chinese model of capitalism, the future will tell. There will always be hope and faith in a better future. There will continue the disputes whether the economic and financial model of the neoliberal system is the only future for the countries of Latin America and the world. Shall we accept the accompanying poverty depends on the social position in which we find ourselves. If we are on top of the financial pyramid and live richly - poverty will be an inevitable "side effect" of development. If we are among the millions of poor whose governments are unable to develop national markets and provide job opportunities - we will want and seek justice and opportunity for a better life. On whom will our prosperity depend - on the government, which cannot fulfill our constitutional rights and freedoms or on the corporate owners who are engaged only with their own profits . Since 1975 until now the world's elites cannot solve the problem of three billion poor and miserable people in the world. What is the guarantee that tomorrow there will be less poor and desperate people?!